The humanization of birth care - Leone, Salvino (Medicina e Morale, 1994)
By now humanization has become one of the topics that a new culture of health care is trying to promote. In this field the humanization of birth care plays a leading role. It is a sector with many inadequacies because of multiple historical conditionings. An overall project of hurnanization should take into consideration the various moments involved in birth. First of all the time of waiting, with the worry, the difficulty in deciding the uncertainties. Then there is the moment of delivery with the problems regarding a better welcome of the birth, the choice between the various methods of analgesia, where to give birth, and finally, the "afterwards", with the typical reactions of the psychological adjustment. Therefore it is a complex panorama in which some results have been achieved but in which there is stili much to be do ne.